Casamino acids enhance growth of Bacteroides melaninogenicus. - Lev, M (1977)
Casamino Acids enhance the growth of Bacteroides melaninogenicus when added to various concentrations of Trypticase. Absence of a peptide, not amino acids, is responsible for the inability of Casamino Acids to support growth.